Yoga in school settings: a research review. Issue 1 (25th February 2016) - Khalsa, Sat Bir S.; Butzer, Bethany
Abstract : Research on the efficacy of yoga for improving mental, emotional, physical, and behavioral health characteristics in school settings is a recent but growing field of inquiry. This systematic review of research on school‐based yoga interventions published in peer‐reviewed journals offers a bibliometric analysis that identified 47 publications. The studies from these publications have been conducted primarily in the United States ( n = 30) and India ( n = 15) since 2005, with the majority of studies ( n = 41) conducted from 2010 onward. About half of the publications were of studies at elementary schools; most (85%) were conducted within the school curriculum, and most (62%) also implemented a formal school‐based yoga program. There was a high degree of variability in yoga intervention characteristics, including overall duration, and the number and duration of sessions. Most of these published research trials are preliminary in nature, with numerous study design limitations, including limited sample sizes (median = 74; range = 20–660) and relatively weak research designs (57% randomized controlled trials, 19% uncontrolled trials), as would be expected in an infant research field. Nevertheless, these publications suggest that yoga in the school setting is a viable and potentially efficacious strategy for improving child and adolescent health and therefore worthy of continued research.